Penerapan Pijat Oksitoksin Terhadap Kelancaran Produksi Asi pada Ibu Post Partum di RSUD dr. Soehadi Prijonegoro Sragen - Maya Ayu Anggraini; Anjar Nurrohmah (Yayasan Literasi Sains Indonesia, 2023)
Exclusive breastfeeding is breastfeeding for the first 6 months without any complementary or additional food. According to WHO, the prevalence of decreased milk production in postpartum mothers is 35.6% of women in the world who cannot breastfeed their babies due to lack of milk production. One effort that can be done to increase milk production is oxytocin massage. To knowing the smooth of breast milk production in postpartum mothers in dr. Soehadi Prijonegoro Sragen Hospital. This type of research is a descriptive case study method. The design used in this research is a pre-test and post test design. A sampling of 2 respondents. The research instrument used a questionnaire to measure breast milk production. There is significant changes to the smooth milk production of postpartum mothers, that is before oxytoxin massage was given 2 respondents were categorized as less and after being given oxytoxin massage 2 respondents were categorized as sufficient. There is a significant increase of oxytocin massage on smooth of the breast milk production in postpartum mothers in dr. Soehadi Prijonegoro Sragen Hospital.